Coatings-electrodes for processing dielectric aluminum oxide ceramics on a wire electrical discharge machine. Issue 1 (June 2021) - Hamdy, K; Okunkova, A A; Fedorov, S V
Abstract: Despite its excellent exploitation properties, the non-conductivity of aluminum-$$$based oxide ceramics significantly limits its application and remains an actual science and technology challenges. An approach to the electrical discharge machining of Al2O3 ceramics using a triple copper coating with a thickness of ∼120 µm as an auxiliary electrode and assisting TiO2-suspension a powder particle concentration of 50, 100, 150 g/l is investigated. The experiments were carried out with unprofiled brass (Ø 0.25 mm) and tungsten (Ø 0.1 mm) wire tool electrodes in a deionized water medium. The highest performance (material removal rate) was obtained for 100 g/l concentration, the pulse frequency of 5 – 8 kHz with a brass tool.